2015
DOI: 10.1097/rlu.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Focal Hepatic 11C-Acetate Activity on PET/CT Scan Due to Lymphoid Hyperplasia

Abstract: A 69-year-old woman complaining of abdominal bloating underwent ultrasonography, which revealed a small lesion in the left lobe of the liver. The lesion had elevated activity of both 18F-FDG and 11C-acetate on PET/CT scan and was suspected of being malignant. Postresection pathological examination demonstrated that this lesion was a focal intrahepatic lymphoid hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In addition to phosphorylation, ubiquitination, which involves the covalent attachment of ubiquitin to target proteins to regulate their half-lives, subcellular localization, activity and conformation, appears to be another important post-translational modification that helps fine-tune protein synthesis ( 20 ). Ubiquitination is a reversible process, and deubiquitinating enzymes (DUBs) cleave ubiquitin moieties from their substrates, to tightly control ubiquitination levels ( 21 ). It has been revealed that many ribosomal proteins, among both the small and large subunits ( 22 , 23 ), as well as several eIFs, including eIF5A ( 24 ), Paip1 ( 25 ), Paip2 ( 26 ), 4E-BP1 ( 27 ) and eIF2B epsilon ( 28 ) are ubiquitinated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to phosphorylation, ubiquitination, which involves the covalent attachment of ubiquitin to target proteins to regulate their half-lives, subcellular localization, activity and conformation, appears to be another important post-translational modification that helps fine-tune protein synthesis ( 20 ). Ubiquitination is a reversible process, and deubiquitinating enzymes (DUBs) cleave ubiquitin moieties from their substrates, to tightly control ubiquitination levels ( 21 ). It has been revealed that many ribosomal proteins, among both the small and large subunits ( 22 , 23 ), as well as several eIFs, including eIF5A ( 24 ), Paip1 ( 25 ), Paip2 ( 26 ), 4E-BP1 ( 27 ) and eIF2B epsilon ( 28 ) are ubiquitinated.…”
Section: Introductionmentioning
confidence: 99%